Biologics use in Indian psoriasis patients - Murlidhar Rajagopalan; Asit Mital (Wolters Kluwer Medknow Publications, 2016)
The biologics currently in use for psoriasis in India are etanercept, infliximab and recently introduced itolizumab and secukinumab. Biosimilars, expected to play a significant role in psoriasis management in future, have also been available for the last few years. Patients with psoriasis may be considered eligible to receive treatment with any of the licensed biologic interventions when they fulfill the eligibility criteria. The decision to proceed with treatment must be made in collaboration with the patient and include a careful assessment of the associated risks and benefits. Etanercept is indicated in moderate to severe psoriasis and moderate to severe psoriatic arthritis with a dose of 25 mg or 50 mg twice weekly. Methotrexate may be recommended as co-medication in certain clinical circumstances, e.g., where it is required for associated arthropathy, or to improve efficacy. Infliximab is indicated in severe psoriasis and moderate to severe psoriatic arthritis. Infliximab therapy should be initiated at a dose of 5 mg/kg at weeks 0, 2 and 6 and disease response assessed at 3 months.In patients who respond, subsequent infusions (5 mg/kg) should be given at 8-week intervals to maintain disease control although long-term data are available only up to 1 year.Interrupted therapy should be avoided given the associated increased risk of infusion reactions and poorer disease control. Itolizumab is indicated in moderate to severe plaque psoriasis. It is given in a dose of 1.6mg/kg iv infusions every 2 weeks for 12 weeks initially and then 1.6mg/kg every 4 weeks up to 24 weeks. Long term data are unavailable. Secukinumab is indicated in moderate to severe plaque psoriasis and psoriatic arthritis.An initial loading dosing regimen of 300 mg secukinumab should be given by subcutaneous injection at weeks 0, 1, 2 and 3 followed by maintenance dose of 300 mg every 4 weeks starting at week 4. To exclude tuberculosis (TB) before anti TNF alfa therapy and therapy with itolizumab, pretreatment chest X-ray and Mantoux skin test currently remain the preferred screening tests in patients not on immunosuppression. During treatment, and for 6 months following discontinuation, a high index of suspicion for TB should be maintained. The effect of secukinumab on TB reactivation is as yet poorly understood, hence, in the Indian scenario, it is better to follow the same guidelines for ruling out latent TB